Mother trees, altruistic fungi, and the perils of plant personification - David G. Robinson; Christian Ammer; Andrea Polle; Jürgen Bauhus; Roni Aloni; Peter Annighöfer; Tobias I. Baskin; Michael R. Blatt; Andreas Bolte; Harald Bugmann; Jerry D. Cohen; Peter J. Davies; et al. (Trends in Plant Science, 2024)

Replace me if you can: Abundance of advance regeneration under canopy trees in a primeval beech forest - R. Petrovska; H. Bugmann; M.L. Hobi; P. Brang (Forest Ecology and Management, 2023)

Survival time and mortality rate of regeneration in the deep shade of a primeval beech forest - R. Petrovska; H. Bugmann; M. L. Hobi; S. Ghosh; P. Brang (European Journal of Forest Research, 2022)
Low mortality rates and slow growth differentiate shade-tolerant from shade-intolerant species and define the survival strategy of juvenile trees growing in deep shade. While radial stem growth has been widely used to explain mortality in juvenile trees, the leaf area ratio (LAR), known to be a key component of shade tolerance, has been neglected so far. We assessed the effects of LAR, radial stem growth and tree height on survival time and the age-specific mortality rate of juvenile Fagus sylvatica L. (European beech), Acer pseudoplatanus L. (sycamore maple) and Acer platanoides L. (Norway maple) in a primeval beech forest (Ukraine). Aboveground and belowground biomass and radial stem growth were analysed for 289 living and 179 dead seedlings and saplings. Compared with the other species, F. sylvatica featured higher LAR, slower growth and a lower mortality rate. The average survival time of F. sylvatica juveniles (72 years) allows it to reach the canopy more often than its competitors in forests with low canopy turnover rate. In contrast, a combination of lower LAR, higher growth rate and higher age-specific mortality rate of the two Acer species resulted in their shorter survival times and thus render their presence in the canopy a rare event. Overall, this study suggests that shade tolerance, commonly defined as a relationship between sapling mortality and growth, can alternatively be formulated as a relationship between survival time and the interplay of growth and LAR.

A synthesis of radial growth patterns preceding tree mortality - Maxime Cailleret; Steven Jansen; Elisabeth M. R. Robert; Lucía Desoto; Tuomas Aakala; Joseph A. Antos; Barbara Beikircher; Christof Bigler; Harald Bugmann; Marco Caccianiga; Vojtěch Čada; Jesus J. Camarero; et al. (Global Change Biology, 2017)
Tree mortality is a key factor influencing forest functions and dynamics, but our understanding of the mechanisms leading to mortality and the associated changes in tree growth rates are still limited. We compiled a new pan‐continental tree‐ring width database from sites where both dead and living trees were sampled (2970 dead and 4224 living trees from 190 sites, including 36 species), and compared early and recent growth rates between trees that died and those that survived a given mortality event. We observed a decrease in radial growth before death in ca. 84% of the mortality events. The extent and duration of these reductions were highly variable (1–100 years in 96% of events) due to the complex interactions among study species and the source(s) of mortality. Strong and long‐lasting declines were found for gymnosperms, shade‐ and drought‐tolerant species, and trees that died from competition. Angiosperms and trees that died due to biotic attacks (especially bark‐beetles) typically showed relatively small and short‐term growth reductions. Our analysis did not highlight any universal trade‐off between early growth and tree longevity within a species, although this result may also reflect high variability in sampling design among sites. The intersite and interspecific variability in growth patterns before mortality provides valuable information on the nature of the mortality process, which is consistent with our understanding of the physiological mechanisms leading to mortality. Abrupt changes in growth immediately before death can be associated with generalized hydraulic failure and/or bark‐beetle attack, while long‐term decrease in growth may be associated with a gradual decline in hydraulic performance coupled with depletion in carbon reserves. Our results imply that growth‐based mortality algorithms may be a powerful tool for predicting gymnosperm mortality induced by chronic stress, but not necessarily so for angiosperms and in case of intense drought or bark‐beetle outbreaks.

Drought response and changing mean sensitivity of European beech close to the dry distribution limit - P. Weber; H. Bugmann; A. R. Pluess; L. Walthert; A. Rigling (Trees, 2013)

Ungulate herbivory modifies the effects of climate change on mountain forests - M. Didion; A. D. Kupferschmid; A. Wolf; H. Bugmann (Climatic Change, 2011)

Improving the establishment submodel of a forest patch model to assess the long-term protective effect of mountain forests - A. Wehrli; P. J. Weisberg; W. Schönenberger; P. Brang; H. Bugmann (European Journal of Forest Research, 2006)

Adapting a growth equation to model tree regeneration in mountain forests - A. Rammig; P. Bebi; H. Bugmann; L. Fahse (European Journal of Forest Research, 2006)

Incidence and distribution of Heterobasidion and Armillaria and their influence on canopy gap formation in unmanaged mountain pine forests in the Swiss Alps - M. Bendel; F. Kienast; H. Bugmann; D. Rigling (European Journal of Plant Pathology, 2006)